Design and implementation of embedded true parallelism jammer system using FGPA-SoC for low design complexity / Hussein Ibrahim Hussein. - Hussein, Hussein Ibrahim (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The aim of this project is to design and implement a frequency jamming which exploit the principle of the true parallelism and obtain the full advantage of the FPGA to guide the missiles to a specific target, the objectives of this research are ; decreased system overall complexity level jamming system, improved operating frequency, consumed chip resources, and improved throughput ; speed up the processing time, increase the processing cores utilities, and reduce the delay occurring in the processing modules.